Peranan Guru Bimbingan Dan Konseling Terhadap Perubahan Sikap Siswa Di SMP Negeri 2 Manado - Sundalangi, Derol Josua; Mangantes, Meisie L. (Peneliti.net, 2023)
This research aims to describe: 1) Factors that influence the truancy behavior of students at SMPN 2 Manado, 2) Efforts of guidance and counseling teachers in dealing with students' truant behavior at SMPN 2 Manado. This type of research is qualitative research which examines the role of guidance and counseling teachers in overcoming students' truant attitudes. Data collection was carried out through observation, interviews and documentation. The data analysis technique used is reducing data, presenting data and drawing conclusions.The research results showed that the role of the guidance and counseling teacher at SMPN 2 Manado in overcoming students' truant attitudes is that first, the guidance and counseling teacher carries out prevention, secondly carries out guidance and counseling service activities in groups and individually, and thirdly presents parents and then groups the problems that arise. faced by students and find solutions to overcome the problems faced by students. And the role of guidance and counseling teachers has been implemented, and students showing truancy are decreasing.